Patologi Birokrasi Lembaga Publik dan Upaya Pencegahannya - Luqman Hakim (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
Bureaucracy is a central pillar of modern governance. Ideally, it is responsible for formulating and implementing policies, delivering high-quality public services, and ensuring effectiveness, transparency, and accountability. However, the Indonesian bureaucracy continues to face serious challenges, as bureaucratic pathologies within public institutions remain deeply rooted. This study aims to explore the underlying causes of bureaucratic pathology in public institutions and to formulate preventive approaches that can be applied systematically and sustainably. This research employs a qualitative method using a library research approach. The primary sources consist of books on organizational theory, bureaucracy, public administration, bureaucratic pathology, and relevant academic journals (previous studies and research findings). The findings indicate that bureaucratic pathology in public institutions essentially stems from intertwined structural, cultural, and individual dimensions. These include organizational structure and design, human resource quality, organizational culture, bureaucratic leadership, political systems, as well as external and legal environments. Preventive approaches to address bureaucratic pathology must be carried out in layered, gradual, and continuous ways. These include structural transformation, human resource capacity building, leadership strengthening, organizational culture reform, enhancement of public ethics, improvement of public accountability mechanisms, and political–legal prevention centered on strengthening the legal system and external oversight.